Hubungan Penilaian Prestasi Kerja Terhadap Promosi Jabatan : Case Study at PT. Bank Rakyat Indonesia Cabang Sutoyo - Arief Yuswanto Nugroho; Anudiyan Amir Mas’ud; Muhammad Maalikal Mulki (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
This research aims to find out whether job performance assessment has a positive and significant effect on employee promotion. This research was conducted from April to July 2017 at PT. Bank Rakyat Indonesia Sutoyo. The population in this research is a total number of 30 employees. The sampling used by this researcher is a "saturated sample," where all members of the population are used as the researcher’s sample, namely 30 employees. The independent variable (X) is the assessment of work performance. The dependent variable (Y) is job promotion. Data analysis was done with simple linear regression analysis. The results of the research show that work performance has a positive and significant effect on the promotion of job positions, meaning that if work performance is improved, it can increase the promotion of the employee’s position.